SISTEM JAJAR LEGOWO (JARWO) STUDI KASUS DESA KARANG TIRTA KECAMATAN LALAN KABUPATEN MUSI BANYUASIN - Setiawati Setiawati; Manisah Manisah (JURNAL AGRIBISNIS TERPADU, 2022)
This research is purposed to know: (1) How much factor production between tabela plants system dan jarwo system is used for rice farming, (2) how much rice farming revenue between tabela plants system and with jarwo plants system, (3) know difference rice farming revenue between tabela plants system and with jarwo plants system. This research hypothesizes that the suspected rice farming revenue jarwo system is not the same as the tabela system. The sampling method in this research is used stratified random sampling, this method have take samples with observed strata or levels in the population, with the following criteria: (1) farmer who used tabela plants system in Karang Tirta village, District Lalan, Musi Banyu Asin Regency, from 664 farmers have taken 20 responded (2) farmers who used jarwo system in Karang Tirta village Laland District Musi Banyuasin Regency, from 172 farmers have taken 20 respondent. The data used is primer data dan secondary, using a list question structure (questioner). The data secondary is obtained from institutions' government, literature, and other sources which connect with this research. The result of this research is no difference significant in revenue between jarwo system and tabela system. Farmers who used tabela system have got revenue Rp. 14.417.994,-/Ha in one season, which is bigger between farmers who used jarwo system and have got average revenue RP. 13.489.051,-/Ha in one season.